Direct Reduction of 1-Bromo-6-chlorohexane and 1-Chloro-6-iodohexane at Silver Cathodes in Dimethylformamide. (10th November 2016) - Rose, John A.; McGuire, Caitlyn M.; Hansen, Angela M.; Karty, Jonathan A.; Mubarak, Mohammad S.; Peters, Dennis G.
Abstract: Cyclic voltammetry and controlled-potential (bulk) electrolyses have been employed to probe the electrochemical reductions of 1-bromo-6-chlorohexane and 1‐chloro-6-iodohexane at silver cathodes in dimethylformamide (DMF) containing 0.050 M tetra- n -butylammonium tetrafluoroborate (TBABF4 ). A cyclic voltammogram for reduction of 1-bromo-6-chlorohexane shows a single major irreversible cathodic peak, whereas reduction of 1-chloro-6-iodohexane gives rise to a pair of irreversible cathodic peaks. Controlled-potential (bulk) electrolyses of 1-bromo-6-chlorohexane at a silver gauze cathode reveal that the process involves a two-electron cleavage of the carbon–bromine bond to afford 1-chlorohexane as the major product, along with 6-chloro-1-hexene, n‐ hexane, 1‐hexene, and 1, 5-hexadiene as minor species. In contrast, bulk electrolyses of 1-chloro-6-iodohexane indicate that the first voltammetric peak corresponds to a one-electron process, leading to production of a dimer (1, 12-dichlorododecane) together with 1-chlorohexane and 6-chloro-1-hexene as well as 1‐hexene and 1, 5-hexadiene in trace amounts. At potentials corresponding to the second cathodic peak, reduction of 1-chloro-6-iodohexane is a mixture of one- and two-electron steps that yields the same set of products, but in different proportions. Mechanistic schemes are proposed to explain the electrochemical behavior of both 1‐bromo-6-chlorohexane and 1-chloro-6-iodohexane.